(3CQLhRI aj GdeLQHGJs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3HOCJ HGSe Gddg ai fXe MSf CPcQ eG LQHJg Whd GdRef s
(3BNQgG (B:s
(3gPG GdPi LQHJg ai YeQi fXeJg ddebJajf CKQi hGdMeO ddg Ydi GdJeGe MeOkG cKjQkG hYdi GdEfYGe s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKGfjIs
(3GfXQ agQS GdWH HQbe (B7s
(3GfXQgG eY CQLhRI ai GdeMejGJ LGeYI HZOGO Qbe (B" 382"s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B304 - (3bSe GdcJGH GdKGfi (B- (3U (B16 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs